Dusty plasma solitons in Vlasov plasmas - Turski, A.J.; Atamaniuk, B.; Żuchowski, K. (Archives of Mechanics, 1999)
Vlasov-Gauss/ Ampère equations for dust-ion-electron plasmas are considered. Dispersion relations are derived for longitudinal dusty plasma waves by use of linearized Vlasov equations. Assuming suitable equilibrium distributions for cold and hot charged particle/grain components, due to negligence of wave-particle interactions and assuming traveling the wave "far field" solutions, fully nonlinear ODE is obtained for SAGDEEV potentials. Examples of Sagdeev potentials and negative solitary waves associated with fully nonlinear dust-acoustic waves (DAW) and dustion acoustic waves (DIAW) are computed.